2021
DOI: 10.1002/oby.23194
|View full text |Cite
|
Sign up to set email alerts
|

Addressing psychosocial health in the treatment and care of adolescents with obesity

Abstract: Obesity affects 158 million youth worldwide and is associated with psychosocial comorbidity. This review describes weight management options utilized by adolescents, including both self-directed weight loss and medically supervised obesity treatment interventions, and associated psychosocial impacts. A majority of adolescents with How to cite this article: Jebeile H, Cardel MI, Kyle TK, Jastreboff AM. Addressing psychosocial health in the treatment and care of adolescents with obesity. Obesity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 96 publications
0
29
0
Order By: Relevance
“…Obesity prevention research is further complicated by ethical and psychosocial health concerns such as weight stigmatization, eating disorder risk, low self-esteem, body dissatisfaction, anxiety, and depression ( 15 18 ). Emerging research demonstrates how supervised obesity treatment can improve psychosocial health for adolescents; however, there is limited research regarding obesity prevention initiatives ( 19 ). Engaging adolescents in the design and development of obesity prevention interventions can address social equity challenges and ethical and psychosocial health concerns ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity prevention research is further complicated by ethical and psychosocial health concerns such as weight stigmatization, eating disorder risk, low self-esteem, body dissatisfaction, anxiety, and depression ( 15 18 ). Emerging research demonstrates how supervised obesity treatment can improve psychosocial health for adolescents; however, there is limited research regarding obesity prevention initiatives ( 19 ). Engaging adolescents in the design and development of obesity prevention interventions can address social equity challenges and ethical and psychosocial health concerns ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…20 It is also a risk factor for sleep disturbances in overweight children, and both obesity and depression are associated with the presence of high inflammatory impacts. 21,22 It is also shown that children who are obese may also have multiple psychosocial challenges, 12 may be subject to weight-based cyber victimization that potentially provokes depression, 23 plus poor academic as well as coping skills that can duly impact their overall mental and physical health significantly and adversely. 24 They may also be at risk for excess overweight status due to excess or poor eating practices as a result of being cared for by depressed caregivers, 17 and that could that well foster signs of negative psychological outcomes such as depression, low self-esteem, and life quality among these youth in their own right.…”
Section: Resultsmentioning
confidence: 99%
“…Alternately, as outlined by Zeller et al, 11 obesity in childhood and adolescence will surely tend to remain a global health challenge of immense proportion and increasing poor health outcomes if timely efforts to address this issue continue to focus largely on eating and physical activity practices to the exclusion of the role of the contribution of multiple mental health attributes on the emergence of obesity and overall future wellbeing of the overweight child. 12…”
Section: Overviewmentioning
confidence: 99%
“…These measures were measured in triplicate and used to calculate BMI (weight kg/height m 2 ), expressed as a standardized score (BMI-SDS) according to age-and sex-specific UK reference data (49). Children are classified as having obesity if they plot above the 98th centile for BMI on relevant sex and age adjusted growth charts (12), and as having morbid obesity if they plot above the 99.6th BMI centile on age and sex-adjusted charts. The presence of a diagnosed co-morbid condition was assessed by review of medical records and common co-morbid conditions included: epilepsy, psoriasis, asthma, dyspraxia, intellectual disability (ID), attention deficit hyperactivity disorder (ADHD), and autistic spectrum disorder (ASD).…”
Section: Methodsmentioning
confidence: 99%